HIEROGLYPHICS CULTURE AS VIZUALIZATION CHANNEL OF JAPAN SOCIETY SOCIOCULTURAL ENVIRONMENT - N. N. Izotova (Концепт: философия, религия, культура, 2017)
Hieroglyphic script culture is the object of the paper; the subject is its role in social and cultural transformations visualization taking place in modern Japanese society. Research methodology includes cognitive approach, which considers the language as a means for learning the world and anthropocentric approach, observing the language in the context of “human factor”. Special attention is given to key events and ideas. Characters Day (Kanji Day) is celebrated on December 12 in Japan. The character with the most votes, selected to represent the events of the year, is announced at a special ceremony at Kiyomizu Temple. Since 1994, this is the date for the announcement of the Kanji of the Year, chosen by the Japanese Kanji Proficiency Society. In 2016 the character (kin; kane) meaning «gold», «money», «metal» was chosen as the character-symbol of the year. Kin garnered 6 605 votes, or 4.33% of the 153 162 ballots cast. The linguoculturological analysis of the results of the «Kanji of the Year» competition undertaken in this article allows for the conclusion that the value of hieroglyphic writing is very important to Japanese social development. Hieroglyphics is an integral, organic part of the culture and art; it is the channel of socio-cultural changes’ visualization. The author points out that in the context of globalization in the modern communicative space hieroglyphics can compete successfully with other semantic-symbolic systems.